The Utilization of Surrounding Technology (Social Media & Business Applications) in Developing and Enhancing MSME Businesses - Erza Sofian; Dadan Ramdhan; Annisa Ulul Fadilah; Cut Nurluthfia Azzahra; Muhammad Hafizh Ariq Muhtarom; Muhammad Hanif Al Muchlisin; Muhammad Mirza Hidayat; Mohamad Irzy Hafiz; Nurhidayah Mardhatillah; Osfiera Novinda Salsabila; Ade Aris Muhamad Thohiri (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
This program aimed to enhance the digital marketing skills of MSME (Micro, Small, and Medium Enterprises) partners by addressing their limited knowledge of social media and digital content creation. Through a series of activities, including training on social media utilization, workshops on content creation using CapCut, and hands-on product photography sessions, participants gained practical skills to improve their marketing efforts. The training focused on teaching strategies for optimizing platforms like Instagram, creating engaging video content by adding audio, text, and auto-text features, and producing high-quality product photos to strengthen their promotional materials. By the end of the program, participants were able to create attractive and professional content, such as videos and images, which were successfully uploaded to Instagram. This initiative empowered MSME partners to leverage technology effectively, enhancing their online presence and competitiveness while fostering innovation in their marketing strategies.